Harmonizing Tradition, Science, and STEM Learning: Empowering Students' Creative Minds with Sound Waves and Local Wisdom - Dyah Sakinah Ika Putri; Botir T Turaqulov (Schrödinger: Journal of Physics Education, 2022)
Purpose of the study: This research aims to develop a STEM module integrated with local kentongan wisdom in physics learning in sound wave material that is feasible, effective and practical to use and can improve students' creative thinking abilities. Methodology: This research uses a Research and Development (R & D) design with the Hannafin and Peck model, which is a product-oriented learning model. The stages in this design model consist of the needs analysis stage, design stage, and development and implementation stage, where each stage is assessed and evaluated. Main Findings: The feasibility of the teaching module was obtained from validation data from 3 expert validators and 3 practitioner validators. Validation shows that it is very valid in the syllabus, lesson plans, test instruments and media. Meanwhile, the module is in the valid category. The reliability of the teaching module with an average of 90.54% shows that all components assessed are in the reliable category. The practicality of the teaching module is obtained from the results of the teacher's response, the implementation of learning is in the very practical category and the student's response is in the practical category. The effectiveness of the teaching module is based on the N-gain of students' generic chemical science skills, with an average N-gain of 79 in the very effective category. Novelty/Originality of this study: The novelty of this research is knowing the effectiveness of developing a STEM module integrated with local wisdom to improve students' creative thinking abilities on sound wave material.